Prolonged in‐hospital stay and higher mortality after Covid‐19 among patients with non‐Hodgkin lymphoma treated with B‐cell depleting immunotherapy. Issue 8 (12th May 2021) - Duléry, Rémy; Lamure, Sylvain; Delord, Marc; Di Blasi, Roberta; Chauchet, Adrien; Hueso, Thomas; Rossi, Cédric; Drenou, Bernard; Deau Fischer, Bénédicte; Soussain, Carole; Feugier, Pierre; Noël, Nicolas; et al.
Abstract: Prolonged Covid‐19 is an emerging issue for patients with lymphoma or immune deficiency. We aimed to examine prolonged length of in‐hospital stay (LOS) due to Covid‐19 among patients with lymphoma and assess its determinants and outcomes. Adult patients with lymphoma admitted for Covid‐19 to 16 French hospitals in March and April, 2020 were included. Length of in‐hospital stay was analyzed as a competitor vs death. The study included 111 patients. The median age was 65 years (range, 19–92). Ninety‐four patients (85%) had B‐cell non‐Hodgkin lymphoma. Within the 12 months prior to hospitalization for Covid‐19, 79 patients (71%) were treated for their lymphoma. Among them, 63 (57%) received an anti‐CD20 therapy. Fourteen patients (12%) had relapsed/refractory disease. The median LOS was 14 days (range, 1–235). After a median follow‐up of 191 days (3–260), the 6‐month overall survival was 69%. In multivariable analyses, recent administration of anti‐CD20 therapy was associated with prolonged LOS (subdistribution hazard ratio 2.26, 95% confidence interval 1.42–3.6, p < 0.001) and higher risk of death (hazard ratio 2.17, 95% confidence interval 1.04–4.52, p = 0.039). An age ≥ 70 years and relapsed/refractory lymphoma were also associated with prolonged LOS and decreased overall survival. In conclusion, an age ≥ 70 years, a relapsed/refractory lymphoma and recent administration of anti‐CD20 therapy are risk factors for prolonged LOS and death for lymphoma patients hospitalized for Covid‐19. These findings may contribute to guide the management of lymphoma during the pandemic, support evaluating specific therapeutic approaches, and raise questions on the efficacy and timing of vaccination of this particular population.